Agricultural land change in the Carpathian ecoregion after the breakdown of socialism and expansion of~the European Union - Patrick Griffiths; Daniel Müller; Tobias Kuemmerle; Patrick Hostert (Environmental Research Letters, 2013)
Widespread changes of agricultural land use occurred in Eastern Europe since the collapse of socialism and the European Union's eastward expansion, but the rates and patterns of recent land changes remain unclear. Here we assess agricultural land change for the entire Carpathian ecoregion in Eastern Europe at 30~m spatial resolution with Landsat data and for two change periods, between 1985–2000 and 2000–2010. The early period is characterized by post-socialist transition processes, the late period by an increasing influence of EU politics in the region. For mapping and change detection, we use a machine learning approach (random forests) on image composites and variance metrics which were derived from the full decadal archive of Landsat imagery. Our results suggest that cropland abandonment was the most prevalent change process, but we also detected considerable areas of grassland conversion and forest expansion on non-forest land. Cropland abandonment was most extensive during the transition period and predominantly occurred in marginal areas with low suitability for agriculture. Conversely, we observed substantial recultivation of formerly abandoned cropland in high-value agricultural areas since 2000. Hence, market forces increasingly adjust socialist legacies of land expansive production and agricultural land use clusters in favorable areas while marginal lands revert to forest.
Keywords: 330; Europe; land use change; agricultural abandonment; fallow land; recultivation; grassland conversion; forest expansion; remote sensing; image compositing; Landsat